Association between uric acid level and incidence of albuminuria in patients with type 2 diabetes mellitus: A 4.5-year cohort study. Issue 41 (15th October 2021) - Lai, Yun-Ju; Chen, Yu-Yen; Ku, Po-Wen; Chen, Li-Jung; Yen, Yung-Feng
Abstract : Abstract: Using animal models and molecular biology researches, hyperuricemia has been shown to instruct renal arteriolopathy, arterial hypertension, and microvascular injury involving the renin-angiotensin system and resulting in renal function impairment. Nevertheless, the association between uric acid levels and the development of albuminuria has been under-investigated in patients with type 2 diabetes mellitus. Patients with type 2 diabetes and regular outpatient visits were recruited from the Puli Branch of the Taichung Veterans General Hospital in Taiwan since January 2014. Demographics, lifestyle features, and medical history were gathered by well-trained interviewers. All participants underwent comprehensive physical examinations, including a biochemical assay of venous blood specimens and urine samples after an 8-hour overnight fast. Participants were followed until June 2018. The primary outcome was the albuminuria incidence. Univariable and multivariable Cox regression analysis were employed to explore the relation between uric acid and incident albuminuria. Uric acid cutoffs for incident albuminuria were determined with the receiver operator characteristic curve. We included 247 qualified subjects (mean age: 64.78 years old [standard deviation = 11.29 years]; 138 [55.87%] men). During a 4.5-year follow-up duration, 20 subjects with incident albuminuria were recognized. Serum uric acid was significantly associated with an increased risk of incident albuminuria (adjusted hazard ratio = 2.39; 95% confidence interval: 1.53–3.75; P  < .001) with potential confounders adjustment. The uric acid cutoff point was 6.9 mg/dL (area under the curve 0.708, sensitivity 60.0%, specificity 84.58%) for incident albuminuria. Serum uric acid was associated with incident albuminuria among patients with type 2 diabetes.